Improving Children's Fine Motor Skills Through Multimodal Stamping Methods at RA Masyithoh 03 Kambangan - Munadhiroh; Moch Bayu Ibrahim S (Educational Insights, 2025)
This study aims to describe the implementation of the multimodal stamping method to improve fine motor skills in early childhood at RA Masyithoh 03 Kambangan. The research used a qualitative case study approach through participatory observation, in-depth interviews with teachers and children, and visual documentation. The findings show that the multimodal stamping method, which combines visual, tactile, and kinesthetic modalities, created an engaging learning experience that effectively developed children’s fine motor skills. Children became more confident, creative, and independent in the stamping activities, while teachers played an important role as facilitators who encouraged exploration. Challenges such as limited materials and a lack of teacher training were addressed through effective collaboration between the school and parents. These findings align with active and holistic learning principles, as outlined in Vygotsky’s and Gardner’s theories. This study recommends that the multimodal stamping method be continuously developed and adapted in early childhood learning, as it not only enhances fine motor skills but also stimulates children’s creativity, social values, and cooperation. The approach provides a solid foundation for holistic child development, supporting their readiness for future academic and social environments.